2013
DOI: 10.3390/md11041256
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Antioxidant Activity of Cell Extracts from Microalgae

Abstract: A growing market for novel antioxidants obtained from non-expensive sources justifies educated screening of microalgae for their potential antioxidant features. Characterization of the antioxidant profile of 18 species of cyanobacteria (prokaryotic microalgae) and 23 species of (eukaryotic) microalgae is accordingly reported in this paper. The total antioxidant capacity, accounted for by both water- and lipid-soluble antioxidants, was evaluated by the (radical cation) ABTS method. For complementary characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(42 citation statements)
references
References 30 publications
(32 reference statements)
4
36
0
2
Order By: Relevance
“…Higher amount of phenolics were found in lipid extracts of Acutodesmus and significant antioxidant levels was observed thus confirming the role of phenolic compounds in antioxidant properties. Similar results from Scenedesmus were obtained by previous studies (Guedes et al, 2013;Aboul-Enein et al, 2003) with higher antioxidants levels and activity. DPPH radical is widely used to test the free radical-scavenging ability of various samples.…”
Section: Discussionsupporting
confidence: 91%
“…Higher amount of phenolics were found in lipid extracts of Acutodesmus and significant antioxidant levels was observed thus confirming the role of phenolic compounds in antioxidant properties. Similar results from Scenedesmus were obtained by previous studies (Guedes et al, 2013;Aboul-Enein et al, 2003) with higher antioxidants levels and activity. DPPH radical is widely used to test the free radical-scavenging ability of various samples.…”
Section: Discussionsupporting
confidence: 91%
“…Cyanobacteria could be one of the most potential source for the production of natural antioxidants. Phenolic acids and flavonoids from plant sources have been well-documented for their antioxidant, free-radical quenching and redox metal ion-chelating affects (Singh et al 2009(Singh et al , 2014Tutour 1990;Apati et al 2003;Hossain et al 2016) but cyanobacteria and microalgae are relatively new source for such compounds in recent years due to their potential benefits and ease of production (Guedes et al 2013;Machu et al 2015). Gallic, chlorogenic, caffeic and ferulic acids identified from plant sources have been known as strong antioxidants and free radical scavengers (Piazzon et al 2012;Babić et al 2015) but their presence in cyanobacteria is scarcely reported and this make these organisms more potential.…”
Section: Resultsmentioning
confidence: 99%
“…Many species exhibit wide range & Dhananjaya P. Singh nabg.nbaim@gmail.com of chemical diversity with characteristic structures coupled with bioactivity that make these organisms a potential candidate for pharmaceuticals (Mandal and Rath 2015). Cyanobacterial species also exhibit potential adaptation strategies against oxidative stresses mainly by the activation of antioxidant defense system that comprises activation of various enzymes (superoxide dismutase, catalase, glutathione reductase and ascorbate peroxidase) (Bharanidharan et al 2013;Guedes et al 2013). Phenylpropanoids and their derivatives are probably the largest group of secondary metabolites isolated from natural sources (plants, microorganisms and microalgal cultures) (Wojdylo et al 2007;Vogt 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies has been indicated that protein content in most of green microalgae is higher than plants (Becker, 1994;Becker, 2007). Microalgae consequently gift to humans and animals positive healthy and reproductive effects (Becker, 2007;Guedes et al, 2013;Choochote et al, 2014;Senosy et al, 2017).…”
Section: Introductionmentioning
confidence: 99%